TECHNOLOGIES OF CLOUD COMPUTING, ICT-OUTSOURCING AND NEW FUNCTIONS OF ICT-DEPARTMENTS OF EDUCATIONAL AND SCIENTIFIC INSTITUTIONS - Bykov, В.Ю. (Journal of Information Technologies in Education (ITE), 2012)
Wide in directions and deep in researches analysis of the present stage of informatization of society and education system is presented. From positions of the system approach the innovative of cause and effect relation, which takes up and details the general problem – the discrepancy of organizational-functional structure of IT departments of educational organizational structures to objective conditions of a modern condition of development of means and technologies of an information society is considered.